Structural capacity in fire of laminated timber elements in compartments with exposed timber surfaces. (15th January 2019) - Wiesner, Felix; Bisby, Luke A.; Bartlett, Alastair I.; Hidalgo, Juan P.; Santamaria, Simón; Deeny, Susan; Hadden, Rory M.
Highlights: Cross-laminated timber compartment fire experimental results are presented. In-depth temperature measurements during the burning and cooling phase. Continued progression of heat into the timber during the cooling phase. Load capacity reduces after auto-extinction of timber compartment fire. Interaction of fire dynamics and load resistance of importance for mass timber. Abstract: In compartment fires with boundaries consisting of exposed mass timber surfaces – for example in compartments with exposed cross-laminated timber (CLT) walls or floors – the thermal penetration depth, i.e. the depth of timber heated to temperatures significantly above ambient behind the char-timber interface, during fire exposure may have a significant influence on the load bearing capacity of structural mass timber buildings, particularly in the decay phase of a real fire. This paper presents in-depth timber temperature measurements obtained during a series of full-scale fire experiments in compartments with partially exposed CLT boundaries, including decay phases. During experiments in which the timber surfaces achieved auto-extinction after consumption of the compartment fuel load, the thermal penetration depth continued to increase for more than one hour, whilst the progression of the in-depth charring front effectively halted at extinction. A simple calculation model is presented to demonstrate that this ongoing progression of thermal penetration continues to reduce the structural load bearing capacity of the CLT elements, thereby increasing the potential for structural collapse during the decay phase of the fire. This issue is considered to be most important for timber compression elements. Currently utilised structural fire design methods for mass timber generally assume a fixed 'zero strength layer' depth to account for thermally affected timber behind the char line; however they make no explicit attempt to account for these decay-phase effects.